"First we eat and then we sell": participatory guarantee systems for alternative sustainability certification of Bolivian agri-food products. Issue 1 (2nd January 2023) - Jacobi, Johanna; Toledo Vásquez, Daniela G.; Solar Alvarez, Jimena M.; Bürgi Bonanomi, Elisabeth
ABSTRACT: Expectations and interest are high in participatory guarantee systems (PGS) as a context-specific alternative to third-party sustainability certification. Self-defined criteria, transparency, trust, and accessibility have made PGS an attractive alternative to exogenous certification in local markets in over 70 countries. There is also increasing interest in the possibilities for participatory certification in international trade for family farm-based products such as cocoa or coffee. Bolivia's PGS was established in 2012. By 2017, the country ranked second (after India) in number of PGS farmers. Since 2019, however, its numbers are declining. Visiting six PGS initiatives, we interviewed 38 persons from production, processing, distribution, support networks, and policymaking on the current situation of PGS in Bolivia; its challenges; its prospects in local, national, and international trade; and the role of Bolivia's governmental PGS support. While PGS certification in Bolivia faces challenges – including high fees, weak consumer demand, and insufficient links to broader value chains – it displays strong potential to make locally managed sustainability certification more accessible. We recommend that decision-makers ensure accessibility and help promote PGS with consumers. Importing countries could support PGS, in particular by incentivizing access of PGS-certified products to their national markets by recognizing them as organic via peer-to-peer certification.